e0705 Comparative study of cardio-ankle vascular index (CAVI) and carotid intima-media thickness - Xiaoyu, Guo; Fangjie, Li (Heart (British Cardiac Society), 2010)
Objective To contrast measurements by two methods of cardio ankle vascular index (CAVI) and carotid intima-media thickness (IMT) and discuss the differences and correlation of two methods for clinical application correctly. Methods The objects are 67 patients with carotid artery ultrasound. We collected the subjects' case history and used VaSera VS-1000 detector to measure CAVI. CAVI≥9.0 is taken as positive, carotid IMT>1.0 mm was positive standards. Results There are 38 cases with CAVI positive results in all the 67 patients, the positive rate of 56.72%. Carotid IMT was detected in 48 cases positive (accounting for 71.64%). compared CAVI and carotid IMT with χ2 test, the results showed that p>0.05, that is to say the measurements of two methods showed no significant statistical difference. In this data we also respectively observed the influential factors of CAVI and carotid IMT using Logistic multiple regression analysis. The result showed that the main influential factor of CAVI and carotid IMT results was age, while none of clinical diagnosis was enrolled the regression equation. Conclusions In this data carotid IMT was made as ultrasound index and CAVI was made as the index of pulse wave velocity, we observed two methods validity to early assess atherosclerosis, the results showed that the detection rate of two methods was overall no significant difference, while carotid IMT has a higher trend than CAVI in positive rate to diagnose atherosclerosis. There are difference and correlation between CAVI and IMT. IMT reflects structural changes in arteries, and CAVI are mainly arterial function index, reflecting changes in arterial stiffness. IMT is mainly used to assess specific certain vascular structural changes, CAVI is mainly used to evaluate systemic arterial stiffness. So uniting CAVI and ultrasonic testing could be evaluated vascular morphology and flexibility function simultaneously, which can more fully grasp the extent of vascular lesion. In the influential factors, age is an independent influential factor of the two methods. While hypertension, hyperlipidaemia, and diabetes were not included in regression equation, we considered it might be correlated with the time of clinical diagnosis, smoking and other factors, or may be due to small sample of this study, which need clinical further large sample in-depth study to confirm.